Desempenho ecofisiológico de mudas de euterpe edulis martius de diferentes estádios de desenvolvimento e implicações para a restauração ecológica - Oliveira, Rodrigo Minici de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Euterpe edulis Martius has a high ecological and economical potential for ecological restoration projects in the Brazilian Atlantic Rainforest, enhancing economic outcomes by providing NTFP as well as food for a wide guild of frugivores. However, as its optimal distribution range includes wetter habitats, the water deficit can constraint successful enrichment plantings in seasonally dry forests. In natural forests, seedling mortality is very high (>95%) and almost null in plants higher than 50 cm, what has been attributed to phenotypic plasticity, although there are no studies proving that. Aiming to increase the chances of success in Euterpe edulis enrichment plantings in seasonally dry forests under restoration process, we conducted two experiments investigating responses to water deficit in the species. In greenhouse conditions, we evaluated plants of two growth stages, represented by classes A (plants with ±15 cm of height and 2 years old) e B (±50 cm height and 4 years), during 3 regimes of water availability (water deficit, rewatering, and subsequent water deficit). The results showed plants of class B presented superior performance when compared to class A in response to water deficit and rewatering, promoting more quickly stomatal closing and opening, what has been assigned to existing morphological differences between classes. When subjected once more to water deficit, the class B presented superior stomatal control when compared to class A and to the control group kept under constant irrigation, demonstrating improvement effect to a recurring cycle of drought. Concurrently, was observed a more efficient adjust on class B regarding to root-to-shoot ratio (0.91±0.32), while class A just reached adjust of 0.51±0.17. The results indicate the possibility of improve water deficit tolerance trough by hardening techniques in nurseries, especially in plants of more advanced growth stages. In the ...

Euterpe edulis Martius possui elevado potencial econômico e ecológico em projetos de restauração da Mata Atlântica, como fonte de produtos florestais não-madeireiros e recursos alimentares a uma ampla guilda de frugívoros. Entretanto, por ser exigente em sombra e especialista de habitats úmidos, o déficit hídrico do solo pode limitar seu estabelecimento em áreas fora de sua zona ótima de distribuição. Em florestas naturais, a mortalidade de plântulas é muito alta (>95%) e quase nula em plantas com mais de 50 cm de altura, o que tem sido atribuído à maior plasticidade fenotípica, embora não haja estudos que comprovem tal característica. Visando ampliar as chances de sucesso em plantios de enriquecimento de Euterpe edulis em áreas de restauração da Floresta Estacional Semidecidual, conduzimos dois experimentos investigando respostas ao déficit hídrico na espécie. Em casa de vegetação, avaliamos plantas de dois estádios de desenvolvimento, representados pelas classes A (plantas com ±15 cm de altura e 2 anos) e B (±50 cm de altura e 4 anos), ao longo de três regimes de disponibilidade hídrica (déficit hídrico, reidratação e nova submissão ao déficit hídrico). Em resposta ao déficit hídrico e à reidratação, a classe B teve desempenho superior à classe A, promovendo o fechamento e abertura estomática mais rapidamente, o que foi atribuído às diferenças morfológicas existentes entre as classes. Na nova submissão ao déficit hídrico, a classe B apresentou controle estomático superior à classe A e ao grupo controle mantido sob contínua irrigação, demonstrando efeito de melhoria a um ciclo recorrente de déficit hídrico. Paralelamente, observamos um ajuste mais eficiente da relação massa seca da raiz e da parte aérea na classe B (0.91±0.32), enquanto a classe A atingiu apenas 0.51±0.17. Esse fato indica a possibilidade de se elevar a tolerância ...
Ecophysiological performance of euterpe edulis martius seedlings at different growth stages and it implications for ecological restoration
Keywords: Palmeiras Irrigação; Irrigação com déficit hídrico; Recuperação ecológica; Mudanças climáticas; Deficit irrigation